Análisis del uso de Gadgets de Realidad Virtual en los usuarios del Shopping de Babahoyo. - Mosquera Briones, Haydee Katerine (2018)
This research work is related to the case study of the analysis of the use of Virtual Reality Gadgets in Babahoyo Shopping users, framed in the sub-line of research, intelligent automation of industrial processes, for the purpose of carrying out an exhaustive analysis of the use of the devices used in the Virtual Reality Island, allowing to identify their advantages and disadvantages. Currently, the evolution of communications involves the transformation of the media, managing to interact with information created artificially. Allowing to live new experiences, creating a simulated environment, one of them is the virtual Reality that allows to live experiences similar to those of the real world allowing the stimuli of sight and hearing among other senses, being a technology in constant evolution, such as 3D images since thanks to this technology we can have Gadgets that allow the visualization of three-dimensional images. The Virtual Reality had its beginning before the 50s, presenting its illustrations and texts referring to an alternative reality that simulated a trip to an unknown world. At the end of the 80 it was the beginning of the world of the videojuegos, since the launching of Virtual Boy of Nintendo was realized, with the purpose of submerging to the user in the videojuego by means of the use of a helmet. Going through the year 2000, Google presented contents of Virtual Reality with its Street View; at the same time the mobiles incorporated gyroscope and accelerometers allowing an object to be visualized towards the north, south, east or west, as well as up, down.